Direct synthesis of a geminal zwitterionic phosphonium/hydridoborate system – developing an alternative tool for generating frustrated Lewis pair hydrogen activation systems. Issue 20 (23rd April 2015) - Yu, Jiangang; Kehr, Gerald; Daniliuc, Constantin G.; Bannwarth, Christoph; Grimme, Stefan; Erker, Gerhard
Abstract : A convenient way to a new class of geminal Mes2 PH + /B(C6 F5 )2 H − pairs is presented. Abstract : A convenient way to a new class of geminal Mes2 PH + /B(C6 F5 )2 H − pairs is presented. It utilizes triflic acid addition to trans -Mes2 PCHCHB(C6 F5 )2 followed by triflate/hydride exchange. Thermally induced ring-closure gave a phosphonium/boratacyclopropane zwitterion8 which formed the Mes2 PH(CHMe)B(C6 F5 )2 H P/B FLP-H2 product10 by subsequent treatment with triflic acid and a silane, or alternatively with dihydrogen at 90 °C. The product10 is an active catalyst for the hydrogenation of a variety of unsaturated organic substrates, including a quinoline derivative. Treatment of compound8 with HB(C6 F5 )2 gave a bifunctional borane14 which selectively reduced carbon monoxide to the formyl stage.